Gender differences in socioemotional skills among adolescents and young adults in Ethiopia, India, Peru and Vietnam - Hossain, M; Jukes, MCH (Young Lives, 2023)
This report uses Young Lives longitudinal data to examine how gender differences in socioemotional skills emerge throughout adolescence, and the socioeconomic and cultural factors that may explain these gaps in Ethiopia, India, Peru and Vietnam. The findings show that gender differences in socioemotional skills associated with empowerment emerge in late adolescence. For example, around the age of 19, boys in Ethiopia, India and Vietnam scored more highly than girls in self efficacy. Similar, but less consistent, patterns were found for self esteem, peer relations and agency. The authors focused analysis of the factors associated with gender differences on self efficacy and agency, where the largest gender differences were found. Having a more equal attitude to gender roles is more strongly associated with the self efficacy of girls, compared to boys, in Ethiopia, and agency in India, reducing the gender gaps in self efficacy in these countries. Among participants aged 22 in Ethiopia and Vietnam, the gender gap in self efficacy was greatest in the poorest tertile, compared to the two wealthier tertiles. The authors conclude that gender differences in socioemotional skills probably emerge as the result of cultural norms. These differences are likely to have implications for the roles that men and women choose to undertake in life. The report has been published as part of Young Lives' research on gender, education and skills. For more about this work, visit our webpage here and follow us on social media for latest updates.